Формування суддівського корпусу в Україні та Польщі: порівняльно-правовий аналіз - Кравчук, В.; Kravchuk, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті проаналізовано вітчизняне та польське законодавство про судоустрій і статус суддів, узагальнено наукові підходи до розуміння категорії «суддівський корпус» у конституційному праві України та Польщі, розглянуто процедури обрання й призначення суддів на посади. Обґрунтовано висновок про те, що суддя є центральним суб’єктом судової влади.In the article the national and Polish legislation of the judicial system and status of judges are examined, basic scientific approaches to the understanding of «judicial case» in the constitutional law of Ukraine and Poland are generalized, procedures for the election and appointment of judges are considered. The article substantiates a conclusion the judge is the central subject of the judiciary. Judges perform the basic functions of justice and the judicial authority and effectiveness of the judicial functions depends on the level of their constitutional and legal status. Using positive foreign experience is undoubtedly helpful for studying not only the order of appointment and electing judges, but also other structural elements of the constitutional and legal status of judges in Ukraine (for example, responsibility, guarantees of their activities and other).
The Formation of the Judicial Case in Ukraine and Poland: the Comparative Legal Analysis.
Keywords: правовий статус суддів; суд; суддівський корпус; legal status of judges; court; judiciary